(untitled) (Global Journal of Science Frontier Research, 2024)
The article identifies the factors influencing the value of the fine structure of the baryonic and dark matter of the universe in the process of its evolution These include the temperature pressure and polarization of dark matter under the influence of the fifth interaction in the direction l b 303o - 27o A strong anisotropy of cosmological parameters was found at a level of 5 in the direction l b 303o - 27o which is in good agreement with the data of other cosmological probes Thus as observations and calculations show the value of fine structure during the evolution of the Universe and its anisotropy has undergone changes depending on temperature density and pressure